BIRD-WATCHING AS A COMPONENT OF ECOTOURISM IN THE USA: A DEMOGRAPHIC AND ECONOMIC ANALYSIS - Olexander Beidyk; Natalia Novosad (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
A concept and essence of bird-watching are reflected as to the component of ecotourism. The analysis of demographic and economic features of watching is given birds in the United States of America, the dynamics of their development and component structure are traced. The features of allocation of tourist charges of bird-watching are investigational in the various sectors of economy of country. Economic efficiency of bird-watching and his contribution is considered to the local economy on the example of city Galveston, state Texas. The insufficient level of development of watching is marked birds as constituent to ecotourism in Ukraine.